Milk Supply Responsiveness in Arid Areas of Western Rajasthan - Gajja, B L; Kalla, Jagdeesh C; Vyas, D L (Annals of Arid Zone, 2016)
The new Co-operative Milk Marketing structure provided under the Operation Flood-I is meant for replacing the traditional milk marketing system in the country. The substitution by the new system would only be possible if milk supply to the plants responds efficiently to the price signals. An attempt has been made in the present study to analyse the price-responsive effectiveness of the new milk marketing system in the arid areas of western Rajasthan. The results of the study unmistakably point to the positive efficiency of marketing signals which, upon proper manoeuvring, would augment milk supplies to overcome the under-utilisation of the capacity of milk plants in the arid areas.